Effective bracing system for transmissionline towers - Nor Najjatulnajihah, Mohd Hamizul (2019)
Transmission line tower which usually affected by the wind load need to be designed to resist the wind load. The transmission line tower should have effective height and effective bracing system in order to give better performance to resist the load. In this research, the transmission line tower was in the form of suspension tower were modelled and designed in Staadpro V8i. Two types of bracing system, K and X system were assigned to the tower. These towers were modeled by considering the effects of tower height which include 39 m, 49 m and 100 m height and were developed with three wind speeds which include 32.5 m/s, 33.5 m/s and 40 m/s in Staadpro V8i. Comparison was made based on the displacement and axial load. It was found that the tower with height 39 m and 49 m gives K bracing system as the effective bracing system and tower with height 100 m showed X bracing system is the effective bracing system. In terms of displacement, 39 m tower with K bracing system that was subjected to 32.5 m/s, 33.5 m/s, and 40 m/s wind speed showed that the displacement was reduced similar to that of 49 m tower height. In contrast, 100 m tower height with K bracing system showed that the displacement increased from the X bracing system. In terms of axial load, 39 m tower subjected to the wind speed of 32.5 m/s, 33.5 m/s, and 40 m/s showed that the K bracing system reduced from the X bracing system, similar to that of 49 m tower. As for the 100 m tower, K bracing system exhibited higher axial load which approximately 46% compared to the X bracing system.